Catherine the Great [videorecording (DVD)] - Chomsky, Marvin J., 1929-; Zeta-Jones, Catherine, 1969-; McGann, Paul; Richardson, Ian, 1934-2007; Blessed, Brian; Rhys-Davies, John; McLachlan, Craig, 1965-; Ferrer, Mel; Moreau, Jeanne, 1928-2017; Sharif, Omar, 1932-2015 (A & E Television Networks : Marketed and distributed by New Video, 2000)
Trapped in a loveless political marriage to the dissolute nephew of the ailing Russian Empress Elizabeth, young German princess Sophia Fredericka bides her time, chooses her lovers carefully and plots her path to the throne. Skillfully manipulating the Russian triumvirate of church, army and aristocracy, she adroitly rides the shifting currents of social change and unrest to become one of Russia's most unforgettable and beloved rulers, Catherine the Great.